All Days 2007
DOI: 10.2118/106185-ms
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Formic Acid Decomposition as a Corrosion Inhibitor Intensifier in Strong Acid Environments

Abstract: For many years formic acid has been used to intensify, or aid in, the performance of acid corrosion inhibitors in hydrochloric acid-based fluids used for stimulation procedures in the oilfield industry. Even so, the picture of how formic acid accomplishes this and under what conditions it functions is incomplete. One theory for how formic acid aids in inhibition is that it undergoes a dehydration reaction to form water and carbon monoxide (CO), a known corrosion inhibitor. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Formic acid has a long history of being used in the oil and gas industry to aid the inhibition performance of corrosion inhibitors (Cassidy et al, 2007;Al-Katheeri et al, 2002). Al-Katheeri et al (2002), for instance noted that at Saudi Aramco, the use of formic and acetic acids is of major importance in well stimulation.…”
Section: Formic Acidmentioning
confidence: 99%
“…Formic acid has a long history of being used in the oil and gas industry to aid the inhibition performance of corrosion inhibitors (Cassidy et al, 2007;Al-Katheeri et al, 2002). Al-Katheeri et al (2002), for instance noted that at Saudi Aramco, the use of formic and acetic acids is of major importance in well stimulation.…”
Section: Formic Acidmentioning
confidence: 99%
“…A curious intensifier example is formic acid (HCOOH) that is thought to work by (A) adsorbing to the metal surface, followed by (B) dehydration to form (C) surface-bound CO. Decomposition of formic acid is catalyzed by HCl acid at high temperatures in the homogeneous phase to generate CO that then migrates to the surface (Figure 3). 47 Formic acid intensifier performance was significantly improved by adding KI when tested for protecting N-80 steel at 28% HCl acid and 135 °C for 4 h. 30 Several other chemicals are used in CIF designs. Surfactants (discussed in section 8) are employed as dispersing agents and for cleaning the metal surface of contaminants to improve inhibitor and intensifier adsorption.…”
Section: Acidizing and Corrosion Inhibitormentioning
confidence: 99%
“…CO can be generated from the dehydration of formic acid, a reaction catalyzed by very strong acids, and that in concentrated HCl can occur at temperatures above 94 o C. Using CO generated from the dehydration of formic acid as a corrosion inhibitor could be more practical than directly dosing CO. Actually, formic acid is often used as an intensifier of the action of common inhibitors like TCA, and it has been recently shown that the intensifying effect might be due to its dehydration to CO [12]. Figure 6 shows the cyclic voltammograms of I825, U420 and N80 in 15% HCl containing 4% (v/v) HCOOH, at 6.9 MPa.…”
Section: Formic Acid As a Precursor Of Co At High Temperature And Prementioning
confidence: 99%
“…Although HCl is not acidic enough to catalyze this reaction at room temperature, it can be catalyzed by hot concentrated HCl [11]. Cassidy et al [12] have recently shown that CO resulting from the dehydration of formic acid in concentrated HCl in the presence of iron-based alloys at high pressure and temperature is most likely responsible for the intensifying action of HCOOH.…”
Section: Introductionmentioning
confidence: 99%